Infected left atrial myxoma with Streptococcus gordonii: case report and literature review - Ruan, Liqin; Chen, Shixiong; Zhang, Jing; Peng, Guiping (Frontiers in Oncology, 2025)
Cardiac myxoma is a relatively common type of benign heart tumor, but infectious myxoma is rare. The symptoms of non-infected cardiac myxoma and infected cardiac myxoma are similar and mostly nonspecific, which can easily lead to delayed diagnosis, missed diagnosis, and delayed treatment. A 57-year-old male patient presented with nonspecific systemic symptoms such as anorexia, fever, and cough, and was initially considered to have gastrointestinal disease or pulmonary infection. Preoperative bacterial culture was negative, and imaging features were consistent with cardiac myxoma. A small amount of vegetation was found attached to the surface of the tumor. Postoperative blood culture, surgical specimen culture, and postoperative blood metagenomic next-generation sequencing (mNGS) examination all showed positive results for Streptococcus gordonii, confirming the diagnosis of infectious left atrial myxoma. For patients with febrile cardiac myxoma, it is crucial to be vigilant against concurrent infections. Blood cultures should be performed before administering antibiotics. In cases where blood cultures are negative, a combination of mNGS, PCR, and transesophageal echocardiography (TEE) should be utilized for differential diagnosis, with particular attention paid to the characteristics of vegetations on the tumor surface.